An Empirical Investigation of the Influence of Qualitative Risk Factors on Canadian Auditors' Determination of Performance Materiality*. (December 2013) - Emby, Craig; Pecchiari, Nicola
Abstract This paper presents the results of a field experiment that tested the effects of various qualitative risk factors suggested by auditing standards and prior literature on practicing Canadian auditors' estimates of performance materiality, a concept introduced by Canadian Auditing Standard (CAS) 320, in the audit of specific accounts in a financial statement audit. Ninety‐four practicing auditors responded to four scenarios and, based on "good" and "bad" versions of six qualitative risk factors, revised or not, as they deemed appropriate, initially established performance materiality for the audit of four different transaction streams/account balances. For all four scenarios, on average, the auditors revised, to a statistically significant degree, performance materiality, downward on the basis of "bad" information and upward on the basis of "good" information. Different combinations of transaction streams/accounts and risk factors were associated with different magnitudes of revision. However, at the level of individual participants, responses were quite varied. Some participants did not revise performance materiality and some even stated that performance materiality should not be revised based on risk‐related information. It may be that the concept of performance materiality as promulgated in CAS 320 and the relationship between overall materiality, performance materiality, and risk requires clarification to provide appropriate guidance for auditors to make performance materiality judgments.